Optimal design and experimental validation of sound absorbing multilayer microperforated panel with constraint conditions. (March 2019) - Yang, Xiaocui; Bai, Panfeng; Shen, Xinmin; To, Sandy; Chen, Liang; Zhang, Xiaonan; Yin, Qin
Graphical abstract: Highlights: Model of sound absorbing coefficient of the multilayer microperforated panel was constructed. Parameters of multilayer microperforated panel were optimized by cuckoo search algorithm. Verifications of optimal parameters were conducted by simulation based on finite element method. Optimal design of multilayer microperforated panel was validated by testing experiments. Abstract: Sound absorption performance of the multilayer microperforated panel can be improved through optimal design of structural parameters. Theoretical model of sound absorbing coefficient of the multilayer microperforated panel with different layers was constructed according to Maa's theory. Structural parameters of the multilayer microperforated panel with layer number from 1 to 8 were optimized through the cuckoo search algorithm with constraint conditions. Preliminary verifications of the achieved optimal parameters were conducted by the analog simulation according to the finite element method. The obtained optimal design of multilayer microperforated panel with no more than 4 layers was finally validated by testing experiments based on the standing wave method, and the optimal average sound absorbing coefficients in the frequency range of 100–6000 Hz were 57.21%, 66.29%, 68.33%, and 69.36%, respectively. Through theoretical modeling, parameter optimization, analog simulation, and experimental validation, an effective method for development of the desired sound absorber was proposed, which will be propitious to promote the applications of the multilayer microperforated panel products in the field of noise reduction.